Restricted and Unrestricted Syntactic Distribution of ar in Bangla - Samrat Halder (Pusat Studi Bahasa dan Publikasi Ilmiah, 2021)
This approach examines the syntactic distribution of ar in Bangla language. Apparently, it seems to occur almost every plausible position across a clause. It may occur clause initially, internally and finally. In some extreme cases, it may occur with each word in a clause. This surface observation does not specify what its exact syntactic distribution is. So, its across clause distributional phenomenon is controversially disputed. In this paper, I shall argue that ar can be restrictedly and unrestrictedly distributed in their respective contexts, thus its apparent multiple syntactic position is a misconception. However, each syntactic distribution either restricted or unrestricted producing a distinct semantic interpretation has specific significance depending on its particular contextual circumstances. This investigation aims at enunciating how every plausible interpretation of ar can be determined based on its restricted and unrestricted syntactic distribution only which in turn reflects its forming of a constituent with the elements following it in a clause. It also shows that the distribution of ar in Bangla is both syntactically and semantically determined.